FLAIR vascular hyperintensities and 4D MR angiograms for the estimation of collateral blood flow in anterior cerebral artery ischemia - Gawlitza, Matthias; Böhme, Johannes; Maros, Máté E.; Groden, Christoph; Förster, Alex (PLOS ONE, 2017)
Purpose To assess FLAIR vascular hyperintensities (FVH) and dynamic (4D) angiograms derived from perfusion raw data as proposed magnetic resonance (MR) imaging markers of leptomeningeal collateral circulation in patients with ischemia in the territory of the anterior cerebral artery (ACA). Methods Forty patients from two tertiary care university hospitals were included. Infarct volumes and perfusion deficits were manually measured on DWI images and TTP maps, respectively. FVH and collateral flow on 4D MR angiograms were assessed and graded as previously specified. Results Forty-one hemispheres were affected. Mean DWI lesion volume was 8.2 (± 13.9; range 0-76.9) ml, mean TTP lesion volume was 24.5 (± 17.2, range 0-76.7) ml. FVH were observed in 26/41 (63.4%) hemispheres. Significant correlations were detected between FVH and TTP lesion volume (ρ = 0.4; P<0.01) absolute (ρ = 0.37; P<0.05) and relative mismatch volume (ρ = 0.35; P<0.05). The modified ASITN/SIR score correlated inversely with DWI lesion volume (ρ = -0.58; P<0.01) and positively with relative mismatch (ρ = 0.29; P< 0.05). ANOVA of the ASITN/SIR score revealed significant inter-group differences for DWI (P<0.001) and TTP lesion volumes (P<0.05). No correlation was observed between FVH scores and modified ASITH/SIR scores (ρ = -0.16; P = 0.32). Conclusions FVH and flow patterns on 4D MR angiograms are markers of perfusion deficits and tissue at risk. As both methods did not show a correlation between each other, they seem to provide complimentary instead of redundant information. Previously shown evidence for the meaning of these specific MR signs in internal carotid and middle cerebral artery stroke seems to be transferrable to ischemic stroke in the ACA territory.